Associations between COVID‐19 and hospitalisation with respiratory and non‐respiratory conditions: a record linkage study. Issue 1 (14th November 2022) - Rowe, Stacey L; Leder, Karin; Dyson, Kylie; Sundaresan, Lalitha; Wollersheim, Dennis; Lynch, Brigid; Abdullahi, Ifrah; Cowie, Benjamin C; Stephens, Nicola; Nolan, Terence M; Sullivan, Sheena G; Sutton, Brett; et al.
Abstract: Objectives: To assess associations between SARS‐CoV‐2 infection and the incidence of hospitalisation with selected respiratory and non‐respiratory conditions in a largely SARS‐CoV‐2 vaccine‐naïve population . Design, setting, participants: Self‐control case series; analysis of population‐wide surveillance and administrative data for all laboratory‐confirmed COVID‐19 cases notified to the Victorian Department of Health (onset, 23 January 2020 – 31 May 2021; ie, prior to widespread vaccination rollout) and linked hospital admissions data (admission dates to 30 September 2021). Main outcome measures: Hospitalisation of people with acute COVID‐19; incidence rate ratios (IRRs) comparing incidence of hospitalisations with defined conditions (including cardiac, cerebrovascular, venous thrombo‐embolic, coagulative, and renal disorders) from three days before to within 89 days of onset of COVID‐19 with incidence during baseline period (60–365 days prior to COVID‐19 onset). Results: A total of 20 594 COVID‐19 cases were notified; 2992 people (14.5%) were hospitalised with COVID‐19. The incidence of hospitalisation within 89 days of onset of COVID‐19 was higher than during the baseline period for several conditions, including myocarditis and pericarditis (IRR, 14.8; 95% CI, 3.2–68.3), thrombocytopenia (IRR, 7.4; 95% CI, 4.4–12.5), pulmonary embolism (IRR, 6.4; 95% CI, 3.6–11.4), acute myocardial infarction (IRR, 3.9; 95% CI, 2.6–5.8), and cerebral infarction (IRR, 2.3; 95% CI, 1.4–3.9). Conclusion: SARS‐CoV‐2 infection is associated with higher incidence of hospitalisation with several respiratory and non‐respiratory conditions. Our findings reinforce the value of COVID‐19 mitigation measures such as vaccination, and awareness of these associations should assist the clinical management of people with histories of SARS‐CoV‐2 infection.